Viśva-sāhitya meṃ Rāmacaritamānasa - Lamagoṛā, Rājabahādura (Śrī Rāmavilāsa Podāra smāraka granthamālā, 1943)
Study of Rāmacaritamānasa, Awadhi poem on Rāma, Hindu deity by Tulasīdāsa, 1532-1623 in the context of world literature.